Los derechos de los contribuyentes en el intercambio de información entre Administraciones tributarias - Cordón Ezquerro, Teodoro (2014)
This paper evidences the need that Tax Administrations have, within a context of economic globalization and business internationalization, to improve and intensify exchange of information in order to achieve an effective and efficient control over the application process of their domestic tax regimes. Considering the benefit maximizing strategy implemented by private economic agents in the global setting, which includes international tax planning as one of their tools, Tax administrations ought to collaborate with each other. Exchange of information is the most suitable mean to implement such collaboration. Within this context, certain taxpayers’ rights could be at stake due to the exchange process; rights that could be properly acknowledged at the domestic level, but could lack similar recognition in an international scenario.